Potential Development of Indonesian Green Sukuk: ANP (Analytic Network Process) - Marta, Gusti (Dinasti Publisher, 2024)
Environmental issues are one of the lessons that need to be considered, especially with the increase in the effect of greenhouse gases (GHG). Indonesia has the enthusiasm to reduce the decline in GHG emissions so as to present reen-based sustainable financing investment products. The purpose of this study was to examine the Indonesian green sukuk with the analytical network process method in order to obtain comparative results. The research used by the researcher is a qualitative research approach with the method used by the Analytic Network Process (ANP). The theoretical studies used include green financing and green sukuk. The findings explain that the development of green sukuk can be influenced by how the government provides alternative green sukuk products that are offered by looking at the reputation of the development of green sukuk so as to generate investor confidence.